Research progress on preparation of cobalt-less/cobalt-free WC-based materials - TANG Yu (Fenmo yejin jishu)
In view of the scarcity of cobalt resources in China and the deficiency of the traditional WC–Co cemented carbides serving in the corrosive medium and high temperature environments, a series of cobalt-less/cobalt-free WC-based materials with good performance was summarized, including the WC-based cemented carbides with other metals or intermetallic compounds instead of Co, the pure WC, and the WC composites reinforced by ceramic phases. The advantages and disadvantages of the cobalt-less/cobalt-free WC-based materials were discussed, and the development trend was forecasted.